CLAIM AN INTERPRETER IN THE CLASS CLEARING THE CASE - TAHA, WEERAYOOT (Rangsit Journal of Law and Society, 2022)
This academic article is intended to study and analyze various problems and obstacles of the law relating to the interpreters at the interrogation stage, in order to the amend the existing provisions concerning such matter based on the information derived from the comparative study of Thai and foreign laws. This study has been mainly conducted by collecting the related Thai and foreign laws, textbooks, theses, thesis papers, research papers, various related academic articles and the online information. The above gathered information are compared, analyzed, and synthesized, to generate the comprehensive and complete laws in such regard. According to the study, although article 13 of Thai Criminal Procedural Code prescribes the procurement of the interpreter, the provision does not cover certain issues. For instance, the qualifications of the interpreter. If the interpreter is not qualified, it can severely damage the investigation process, and may cause the unlawful investigation. Such article also does not indicate the sources and the methods to procure the interpreter which are essential as well. Moreover, the research has found that the laws regarding the interpretation in the investigation process of the United States of America and the United Kingdom are very effective, and should be endorsed to solve the problems and the obstacles in Thai laws regarding such issue.